2012
DOI: 10.1016/j.biortech.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Micro-environment characteristics and microbial communities in activated sludge flocs of different particle size

Abstract: h i g h l i g h t s" Microelectrodes and molecular culture-independent techniques were applied. " The micro-environment and bacteria in flocs with different size were detected. " The DO, NH 4 + and NO 3 À concentration were distinct in flocs of different size." The bacterial population was closely related to the micro-environment in flocs.a r t i c l e i n f o b s t r a c tMicroorganisms in activated sludge flocs (ASF) play important roles in the wastewater treatment process. However, the interplay between mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…S3) in this study, and their closest relative sequences are shown in Table S7. Bacteria belonging to genera Proteobacteria, Firmicutes, and Bacteroidetes were abundant in all the activated sludge processes, which was consistent with Han's (Han et al, 2012) study involving the treatment of municipal wastewater. Fusobacteria, Planctomycetes, and Gammaproteobacteria (including Plesiomonas, Pseudomonas, Vibrio, and Thiothrix) were the most abundant bacteria in this system.…”
Section: Microbial Community Analysissupporting
confidence: 89%
“…S3) in this study, and their closest relative sequences are shown in Table S7. Bacteria belonging to genera Proteobacteria, Firmicutes, and Bacteroidetes were abundant in all the activated sludge processes, which was consistent with Han's (Han et al, 2012) study involving the treatment of municipal wastewater. Fusobacteria, Planctomycetes, and Gammaproteobacteria (including Plesiomonas, Pseudomonas, Vibrio, and Thiothrix) were the most abundant bacteria in this system.…”
Section: Microbial Community Analysissupporting
confidence: 89%
“…A hybridization solution that contained 5 ng mL À1 of probe was applied to the slide. The FISH procedure was similar to that described by Han (Han et al, 2012). The biomass on the slide was stained with DAPI solution.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Facultative anaerobic or anaerobic microorganisms are abundant in environments with an oxygen volume fraction of less than 2% (Lee et al, 2001). With the innovation of microelectrodes, detection of the oxygen distribution in microenvironments is now possible and interesting oxygen microelectrode studies have been performed, including in nitrifying/denitrifying biofilms (Stief et al, 2003) and a single floc (Tsai et al, 2008;Han et al, 2012). Microelectrode measurements provide reliable and in situ information on the activity of microorganisms in biofilms formed on media (Chae et al, 2012).…”
Section: Introductionmentioning
confidence: 99%